INVESTMENT RISK IN CRYPTOCURRENCY TRANSACTIONS IN INDONESIA - Agustina, Elvira (Indragiri Research Center (ingreat), 2023)
This research was conducted on Investment Risk in Cryptocurrency Transactions in Indonesia. The purpose of this study is to find out how the risks of investing and cryptocurrency transactions in Indonesia are. Source of data in this study using secondary data. Then using a qualitative descriptive research type because researchers want to find facts about